FEATURES OF THE USE OF MAIN VERBS IN KOREAN AS AUXILIARY VERBS - Kamalova Shirin (International Engineering Journal For Research & Development, 2022)
This scientific article discusses main verbs in the Uzbek and Korean languages and their use in the meaning of auxiliary verbs, the addition of auxiliary verbs to the text, their role in teaching foreign languages, their meaning is considered.